Porous catalytic membrane, membrane electrode assembly and water electrolysis device

By using porous polymer films formed by interwoven randomly arranged nanofibers as catalyst support, the problem of ionomers used in existing electrolytic water systems is solved, and efficient catalyst utilization and electrode performance are achieved.

CN119824448APending Publication Date: 2025-04-15HONG KONG UNIV OF SCI & TECH (GUANGZHOU)

Patent Information

Application Number
CN202510299698.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-13
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the existing PEM and AEM electrolytic water systems, the use of ionomers has problems such as catalytic active site shielding, high cost, reduced performance and shortened life. The preparation process is complex, which increases production difficulty and manufacturing cost.

Method used

The porous polymer film formed by interwoven nanofibers in random arrangement is used as the support for the catalyst, and the catalyst is uniformly deposited on the surface of the nanofiber by physical or chemical methods to get rid of its dependence on ionomers.

Benefits of technology

The efficiency of the catalyst utilization is significantly improved, the amount of precious metal catalyst is used, the manufacturing cost is reduced, and the interface characteristics between the catalyst layer and the ion exchange membrane are optimized, which improves the mass transfer efficiency, catalytic activity and long-term stability of the electrolytic water electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824448A_ABST
    Figure CN119824448A_ABST
Patent Text Reader

Abstract

The invention discloses a porous catalytic membrane, a membrane electrode assembly and a water electrolysis device, and relates to the technical field of new energy. The porous catalytic membrane provided by the invention comprises a porous polymeric membrane formed by interweaving randomly arranged nanofibers, and a catalyst covering the surfaces of the nanofibers, the porous polymeric membrane has a self-supporting structure and a large specific surface area, and provides a large number of loading sites for the catalyst; the catalyst can be directly anchored on the nanofiber of the porous polymeric membrane through a physical or chemical preparation method, uniform dispersion is realized, and no ionomer is needed for coating, so that the problems of high cost and performance reduction caused by use of the ionomer are avoided, the exposure degree of catalytic active sites is remarkably improved, and the catalytic activity of the catalyst is improved. Therefore, the utilization efficiency of the catalyst is improved and the dosage of the noble metal catalyst can be reduced; in addition, the porous catalytic membrane and the ion exchange membrane have excellent interface contact characteristics, and integrated combination of the porous catalytic membrane and the ion exchange membrane is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of new energy technology, and in particular to a porous catalytic membrane, a membrane electrode assembly and a water electrolysis device. Background Art

[0002] As the global demand for clean energy and a low-carbon economy continues to grow, hydrogen energy, as an efficient and pollution-free energy carrier, is receiving more and more attention. Proton exchange membrane (PEM) water electrolysis technology and anion exchange membrane (AEM) water electrolysis technology, due to their respective advantages, have become the core paths for large-scale production of green hydrogen. PEM water electrolysis technology is known for its high current density, fast dynamic response and compact system design, while AEM water electrolysis technology has attracted much attention because it can use non-precious metal catalysts under alkaline conditions, reduce costs and improve system durability. However, whether it is a PEM or AEM water electrolysis system, its overall performance and economy largely depend on the design and preparation process of the electrode.

[0003] At present, PEM water electrolysis electrodes usually use precious metals (such as platinum, iridium, etc.) as catalysts, and are combined with ionomers (such as perfluorosulfonic acid polymers) as binders and mass-conducting media to achieve uniform dispersion of the catalyst, good electronic conductivity and proton transport capacity; similarly, AEM water electrolysis electrodes often use transition metal-based catalysts (such as nickel, cobalt, iron oxides or hydroxides), and may introduce ion-conducting polymers or alkaline ionomers (such as quaternary ammonium polymers) to enhance the hydroxyl ion (OH ﹣) conduction and electrode structure stability. However, whether in PEM or AEM systems, the use of ionomers has several common problems and technical bottlenecks: under the action of ionomers, some catalytic active sites may be shielded or coated, limiting the effective contact between the catalyst and the reactants (such as water molecules or hydroxyl ions), thereby reducing the utilization rate of the catalyst. High loadings of precious metals (such as platinum or iridium in PEM) or specific catalyst materials (such as optimized transition metal compounds in AEM) significantly increase the cost of water electrolysis equipment; although the bonding and ion conduction functions of ionomers in electrodes are indispensable, there may be microscopic defects at the interface between them and the catalyst, support or ion exchange membrane, resulting in local electronic conduction or ion transport (protons or hydroxyl ions) being blocked, thereby reducing the reaction kinetics efficiency of the electrode; during long-term operation, ionomers may be chemically degraded (such as in acidic environments). The chemical stability of ionomers in PEM systems is limited by oxidative stress and high temperature under acidic conditions, while the alkaline stability of ionomers in AEM systems faces the challenges of hydroxyl ion attack and polymer chain breakage. In addition, the component optimization, uniform dispersion and stability control of ionomers place high demands on the precise regulation of process parameters. Whether it is the acid compatibility of ionomers in PEM systems or the alkaline tolerance and ionic conductivity of ionomers in AEM systems, their preparation processes require complex process design and quality control, which not only increases the difficulty of production, but also significantly increases the manufacturing cost, limiting the economic feasibility of both in large-scale applications. Summary of the invention

[0004] The present application provides a porous catalytic membrane, a membrane electrode assembly and a water electrolysis device, aiming to provide an ideal platform for uniform loading of the catalyst and get rid of the dependence on ionomers.

[0005] The porous catalytic membrane provided in the present application comprises:

[0006] A porous polymer membrane formed by randomly arranged nanofibers interwoven; and,

[0007] A catalyst is covered on the surface of the nanofiber.

[0008] Optionally, the porous polymer membrane is made of polyolefin.

[0009] Optionally, the porous polymer membrane is prepared by the following process steps:

[0010] Step 1, mixing petrolatum, polyolefin and antioxidant, wherein the petrolatum comprises vaseline, white vaseline or a semi-solid mixture of hydrocarbons;

[0011] Step 2, stirring petrolatum, polyolefin and antioxidant to form a suspension;

[0012] Step 3, supplying the suspension to an extruder to produce gel filaments;

[0013] Step 4, pressing the gel filaments to form a gel film;

[0014] Step 5, stretching the gel film to a preset size;

[0015] Step 6, placing the stretched gel film under annealing temperature;

[0016] Step 7, extracting petrolatum from the stretched gel film.

[0017] Optionally, the porous polymer membrane is biaxially oriented, and nanofibers of the porous polymer membrane comprise a shuffle structure.

[0018] Optionally, the porous polymer membrane is made of ultra-high molecular weight polyethylene, and the molecular weight of the ultra-high molecular weight polyethylene is 1 million to 15 million g / mol.

[0019] Optionally, the pore size of the porous polymer membrane is 15-500 nm.

[0020] Optionally, the porosity of the porous polymer membrane is 15%-90%.

[0021] Optionally, the tensile strength of the porous polymer membrane is 100-2000 MPa.

[0022] Optionally, the elongation at break of the porous polymer membrane is 5-300%.

[0023] Optionally, the diameter of the nanofiber is 1-100 nm.

[0024] Optionally, the thickness of the porous polymer membrane is 15-500 nm.

[0025] Optionally, the catalyst loading is 0.01-0.5 mg / cm 2 .

[0026] Optionally, the catalyst is at least one of a transition metal, a transition metal alloy, and a compound formed by a transition metal and a Group VA or Group VIA element.

[0027] Optionally, the catalyst is deposited on the surface of the nanofiber by at least one of physical vapor deposition, atomic layer deposition, electrochemical deposition, solution dip coating, spray deposition, sol-gel method, and chemical in-situ growth.

[0028] The membrane electrode assembly provided in the present application comprises an ion exchange membrane and an anode catalyst layer and a cathode catalyst layer respectively bonded to both sides of the ion exchange membrane, and at least one of the anode catalyst layer and the cathode catalyst layer is the porous catalyst membrane described above.

[0029] Optionally, the porous catalytic membrane is combined with the ion exchange membrane by a hot pressing transfer process.

[0030] Optionally, in the hot pressing transfer process, the processing temperature is 100° C.-130° C., the pressure applied during hot pressing is 2-5 MPa, and the hot pressing time is 1-10 min.

[0031] Optionally, the ion exchange membrane can be prepared by the following method:

[0032] A solution or dispersion containing ion exchange membrane material is applied to at least one surface of the porous catalyst membrane, and the ion exchange membrane is formed on the porous catalyst membrane after being cured.

[0033] The water electrolysis device provided in the present application includes the porous catalytic membrane described above, or the membrane electrode assembly described above.

[0034] This application has the following beneficial effects:

[0035] The technical solution of the present application adopts a porous polymer membrane formed by randomly arranged nanofibers interwoven as a carrier of the catalyst. The porous polymer membrane has a self-supporting structure and a large specific surface area, which provides a large number of loading sites for the catalyst. The catalyst can be directly anchored on the nanofibers of the porous polymer membrane by a physical or chemical preparation method, so that the catalyst can be evenly dispersed in the porous polymer membrane without the need for ionomer coating, avoiding the high cost and performance degradation caused by the use of ionomers, and significantly improving the exposure of catalytic active sites, thereby significantly improving the utilization efficiency of the catalyst and reducing the amount of precious metal catalysts. In addition, the porous catalytic membrane based on the porous polymer membrane and the ion exchange membrane (usually made of polymer material) have excellent interface contact characteristics, which helps to achieve an integrated combination of the two. Therefore, the technical solution of the present application gets rid of the dependence on ionomers, improves the catalyst utilization rate, reduces the membrane electrode manufacturing cost and optimizes the interface characteristics between the catalyst layer and the ion exchange membrane, which can significantly improve the mass transfer efficiency, catalytic activity and long-term stability of the water electrolysis electrode, and provides a solid technical support for high-performance, high-reliability and low-cost hydrogen energy preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0037] Figure 1 The surface morphology SEM images of the ultra-high molecular weight polyethylene films in some embodiments of the present application;

[0038] Figure 2 The surface morphology SEM images of Pt-PE electrodes with different sputtering thicknesses in some embodiments of the present application;

[0039] Figure 3 This is a cross-sectional SEM image of a PEM membrane electrode assembly prepared by hot-pressing transfer of a Pt-PE electrode in some embodiments of the present application;

[0040] Figure 4 A schematic structural diagram of an embodiment of a magnetron sputtering device used in an embodiment of the present application;

[0041] Figure 5 This is a schematic diagram of the structure of some embodiments of the water electrolysis device of the present application;

[0042] Figure 6 The linear sweep voltammetry curves of the experimental group and the control group in the hydrogen evolution reaction in some embodiments of the present application;

[0043] Figure 7 This is a bar graph comparing the overpotentials of the experimental group and the control group in the hydrogen evolution reaction in some embodiments of the present application;

[0044] Figure 8 A comparison of linear sweep voltammetry curves of a 40 nm Pt-PE electrode and a commercial Pt / C electrode after 10,000 cyclic voltammetry tests with those of the initial state in some embodiments of the present application;

[0045] Fig. 9 The AC impedance spectra of the experimental group and the control group in the hydrogen evolution reaction in some embodiments of the present application;

[0046] Fig.10 The voltage-current density curve of the 45nm Pt-PE electrode in PEM water electrolysis in some embodiments of the present application;

[0047] Fig.11 The voltage-current density curves of Pt-PE electrodes with different sputtering thicknesses in PEM water electrolysis in some embodiments of the present application;

[0048] Fig.12 The voltage-current density curves of 45nm Pt-PE electrode and commercial Pt / C electrode in PEM water electrolysis in some embodiments of the present application;

[0049] Fig.13 The voltage-current density curve of 45nm Pt-PE electrode in PEM water electrolysis under different temperature conditions in some embodiments of the present application;

[0050] Fig.14 The voltage-current density curves of the 45nm Pt-PE electrode in the PEM electrolysis water in the initial state and after 40,000 accelerated aging cycles in some embodiments of the present application;

[0051] Fig.15 This is a graph showing the long-term stability test data of a 45nm Pt-PE electrode at different current densities in some embodiments of the present application;

[0052] Fig.16 The Pt-PE electrodes prepared in some embodiments of the present application are shown;

[0053] Fig.17 The PEM membrane electrode assembly prepared according to some embodiments of the present application is shown.

[0054] Description of Figure Numbers:

[0055] 1. Cavity; 2. Target electrode; 3. Target; 4. Rotating stage; 5. Power supply; 6. Ar ions; 7. Pt atoms; 100. Anode plate; 101. Oxygen outlet; 200. Cathode plate; 201. Hydrogen outlet; 300. Sealing gasket; 400. Titanium felt; 500. Carbon paper; 600. Membrane electrode assembly. DETAILED DESCRIPTION

[0056] In order to make the purpose, features, and advantages of the invention of this application more obvious and easy to understand, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the drawings in the embodiments of this application. Obviously, the embodiments described below are only part of the embodiments of the present invention, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0057] A first aspect of the present application provides a porous catalytic membrane used as a catalytic layer of a membrane electrode assembly, aiming to provide an ideal platform for uniform loading of catalysts, thereby getting rid of dependence on ionomers.

[0058] See also Figure 1 and Figure 2The porous catalytic membrane provided in the embodiment of the present application includes: a porous polymer membrane formed by randomly arranged nanofibers interweaving, and a catalyst covering the surface of the nanofibers.

[0059] The embodiment of the present application uses a porous polymer membrane formed by randomly arranged nanofibers as a carrier of the catalyst. The porous polymer membrane has a large specific surface area and provides a large number of loading sites for the catalyst. The catalyst can be directly anchored on the nanofibers of the porous polymer membrane through physical or chemical preparation methods, so that the catalyst can be evenly dispersed in the porous polymer membrane without the need for ionomer coating, thus avoiding the high cost and performance degradation problems caused by the use of ionomers, and significantly improving the exposure of catalytic active sites (the exposure rate of catalytic active sites in the traditional slurry method is about 50%, while the exposure rate of catalytic active sites in the embodiment of the present application can exceed 90%), thereby significantly improving the utilization efficiency of the catalyst and reducing the amount of precious metal catalyst used.

[0060] In the embodiments of the present application, the porous polymer membrane is prepared from polyolefins, including but not limited to polyethylene, polypropylene, polybutene, olefin binary copolymers, and olefin multi-polymers.

[0061] The inventor's research team has conducted in-depth research on the preparation of nanoporous ultra-high molecular weight polyethylene films in previous work. Different polyolefin materials can be prepared by referring to the preparation process of ultra-high molecular weight polyethylene films.

[0062] The porous polymer membrane suitable for the embodiment of the present application can be prepared by the following process steps:

[0063] Step 1, mixing petrolatum, polyolefin and antioxidant, wherein the petrolatum includes vaseline, white vaseline or a semi-solid mixture of hydrocarbons.

[0064] In step 2, petrolatum, polyolefin and antioxidant are stirred to form a suspension.

[0065] Step 3, supplying the suspension to an extruder to produce gel filaments.

[0066] Step 4, pressing the gel filaments to form a gel film.

[0067] Step 5, stretching the gel film to a preset size.

[0068] Step 6, placing the stretched gel film under annealing temperature.

[0069] Step 7, extracting petrolatum from the stretched gel film.

[0070] In some embodiments, the porous polymer membrane is made of ultra-high molecular weight polyethylene, and the molecular weight of the ultra-high molecular weight polyethylene is 1 million to 15 million g / mol.

[0071] The prepared porous polymer membrane has a nanoporous structure, and by controlling the annealing temperature and cooling rate, the polymer melt and solution can be transformed into a cascade self-reinforced composite crystal structure through flow induction; by stretching through a biaxial stretching device, or by stretching in two perpendicular directions in sequence through a uniaxial stretching device, an ultra-high molecular weight polyethylene porous membrane with biaxial orientation can be obtained.

[0072] Among them, the shish-kebab structure refers to the nanofiber with a straight chain as the core, around which many folded chain segments grow. The straight chain crystal part is formed by the polymer molecular chain stretched and arranged along the stress direction, and has a high degree of orientation and regularity. The folded chain segment crystal is a thin sheet-like crystal formed by the molecular chains arranged and stacked in a folded manner on the surface of the straight chain crystal. The shish-kebab structure can significantly improve the mechanical properties and thermal stability of the porous polymer membrane.

[0073] Biaxial orientation means that when preparing porous polymer membranes, tensile forces are applied to the polymer material in two mutually perpendicular directions (usually horizontal and vertical directions) to change the stacking mode of polymer molecular chains. This biaxially oriented porous polymer membrane improves the mechanical strength of the membrane and can enhance the mechanical properties of the polymer, such as tensile strength, tear strength, and toughness.

[0074] The embodiments of the present application preferably have a porous polymer membrane with biaxially oriented and shuffled crystal structure nanofibers. Such a porous polymer membrane has a self-supporting structure and can be used as a matrix material for loading catalysts without an additional carrier, thereby avoiding the interface contact resistance problem that may be introduced by traditional carriers such as carbon paper or titanium felt. The prepared porous polymer membrane has the characteristics of high strength and ultra-thinness, can be prepared on a large area, and thus has the potential for industrialization.

[0075] In the preparation process of the porous polymer membrane, the mechanical strength, pore structure and thickness of the porous polymer membrane can be designed by adjusting the raw material ratio, extrusion and stretching process parameters, annealing temperature and cooling rate to meet the requirements of the porous polymer membrane in the embodiments of the present application.

[0076] In some embodiments, the pore size of the porous polymer membrane is 15-500 nm. Pore sizes in this range are critical to ensure that reactant molecules can smoothly enter the pores and contact the active sites, while avoiding the problem of gas diffusion restriction caused by too small pore sizes.

[0077] In some embodiments, the porous polymer membrane has a porosity of 15%-90% and has good air permeability.

[0078] The embodiments of the present application can increase the contact area between the catalyst and the porous polymer membrane by adjusting the pore structure of the porous polymer membrane. The optimization of the pore structure design can also effectively improve the conductivity of the membrane electrode and increase the catalytic reaction rate. At the same time, the excellent air permeability of the film helps to quickly diffuse the generated gas during the electrolysis process and reduce mass transfer problems caused by bubble blockage.

[0079] In some embodiments, the porous polymer membrane has a tensile strength of 100-2000 MPa.

[0080] In some embodiments, the elongation at break of the porous polymer film is 5-300%.

[0081] The porous polymer membrane provided in the embodiment of the present application has moderate flexibility, so that the porous polymer membrane can effectively relieve thermal stress and avoid cracking of the catalyst layer during the subsequent deposition of the catalyst and the combination with the ion exchange membrane. It also allows the porous catalytic membrane to be combined with the ion exchange membrane by hot pressing transfer, ensuring uniform interfacial pressure transfer during the hot pressing process, and ultimately achieving a tight and integrated combination of the catalytic layer and the ion exchange membrane.

[0082] In some embodiments, the diameter of the nanofibers is 1 nm-100 nm, and they have good mechanical properties, air permeability and moisture permeability, and are also convenient for the attachment of catalysts.

[0083] In some embodiments, the thickness of the porous polymer membrane is 15-500 nm. The ultra-thin property ensures that the porous catalytic membrane has a lower charge transfer resistance during the electrolysis process, which helps to improve the electrolysis efficiency.

[0084] In the embodiments of the present application, the catalyst includes but is not limited to transition metals, transition metal alloys, and compounds formed by transition metals and Group VA or Group VIA elements; transition metal elements generally include platinum, iridium, ruthenium, iron, nickel, cobalt, etc., and Group VA or Group VIA elements that can form compounds therewith generally include oxygen, sulfur, nitrogen, phosphorus, etc.

[0085] Among them, in the application of water electrolysis, oxygen evolution reaction occurs at the anode, which requires the catalyst to have good catalytic activity, stability and corrosion resistance; in PEM (proton exchange membrane) systems, the most commonly used anode catalyst materials include iridium-based materials (such as IrO2) and ruthenium-based materials (such as RuO2); in AEM (anion exchange membrane) systems, nickel-based materials (such as Ni(OH)2 and its derivatives) and cobalt-based materials can be used as anode catalysts (AEM).

[0086] The hydrogen evolution reaction occurs at the cathode of water electrolysis, which requires the catalyst to have a low hydrogen evolution overpotential, high catalytic activity and good stability. Platinum is the most commonly used hydrogen evolution catalyst; in addition, some non-precious metal materials such as molybdenum disulfide, cobalt phosphide, cobalt nitride and their derivatives can also be used as hydrogen evolution catalysts.

[0087] In some embodiments, the catalyst loading is 0.01-0.5 mg / cm 2 .

[0088] Compared with the method of preparing the catalytic layer with ionomer slurry widely used in the prior art, the embodiment of the present application can achieve excellent catalytic performance and stability while using a porous polymer membrane as a carrier to greatly increase the exposure rate of catalytic active sites, thereby greatly reducing the amount of precious metal catalysts such as iridium, ruthenium, platinum or specific catalyst materials used, thereby reducing the cost of hydrogen production.

[0089] In the embodiments of the present application, the catalyst can be covered on the nanofiber surface of the porous polymer membrane by a physical or chemical preparation method, including but not limited to physical vapor deposition, atomic layer deposition, electrochemical deposition, solution dipping, spray deposition, sol-gel method, chemical in situ growth, etc., or any combination of these process methods to achieve uniform or selective deposition of the catalyst on the porous polymer membrane.

[0090] Specifically, physical vapor deposition refers to the process of converting materials into atomic, molecular or ionic states by physical means under a vacuum environment, and then depositing them on the surface of a substrate via gas phase transport to form the desired thin film layer. For example, magnetron sputtering and evaporation processes can uniformly deposit high-purity metals or metal oxides on the surface of nanofibers of porous polymer membranes.

[0091] Atomic layer deposition forms a deposited film by alternately introducing pulses of gaseous precursors into a reaction chamber, where chemical adsorption and reaction occur on the surface of the deposition substrate. Usually only one layer of atoms or molecules is deposited in each cycle. By repeating the cycle continuously, the deposition thickness can be precisely controlled.

[0092] The solution dipping method is to evenly disperse the catalyst particles in a mixture of a dispersant and a binder, and then immerse the porous polymer membrane in it. After adsorption, precipitation and drying steps, the catalyst particles are finally attached to the nanofibers. The operation is simple and suitable for temperature-sensitive porous polymer membrane materials. Solution spray deposition also uses a solution containing a catalyst. The difference is that by spraying a solution containing a catalyst on the surface of the porous polymer membrane, the catalyst can be more evenly attached to the surface of the porous polymer membrane. The sol-gel method makes the catalyst precursor evenly dispersed in the sol system. During the process of sol to gel transformation, the catalyst precursor can maintain a highly dispersed state. The catalyst particles finally formed have a small particle size and are evenly distributed. The sol-gel can be evenly formed into a film on the surface of the porous polymer membrane by spin coating.

[0093] In the electrochemical deposition process, a layer of carbon film or other conductive material can be pre-prepared on the surface of the porous polymer membrane, which is placed in an electrolytic cell to deposit the catalyst using electrochemical principles. Chemical in situ growth promotes nucleation through the surface functional groups or pre-coatings of the porous polymer membrane, and the catalyst is directly synthesized on the nanofibers of the porous polymer membrane by strictly controlling reaction conditions such as pH and temperature.

[0094] A second aspect of the present application provides a membrane electrode assembly.

[0095] The membrane electrode assembly provided in the embodiment of the present application includes an ion exchange membrane and an anode catalyst layer and a cathode catalyst layer respectively bonded to both sides of the ion exchange membrane, and at least one of the anode catalyst layer and the cathode catalyst layer adopts the porous catalyst membrane provided in the above embodiment.

[0096] The ion exchange membrane can be a proton exchange membrane, a cation exchange membrane or an anion exchange membrane; for example, in the application of water electrolysis, the proton exchange membrane can be a perfluorosulfonic acid ion exchange membrane or its modified derivatives, which have excellent proton conductivity and chemical durability, or it can be an anion exchange membrane formed by a quaternary ammonium polymer or its functionalized variants, which has excellent hydroxyl ion conductivity and alkaline chemical stability.

[0097] In some embodiments, the porous catalytic membrane can be combined with the ion exchange membrane by a hot press transfer process.

[0098] Specifically, porous polymer membranes have excellent interface contact properties with most ion exchange membrane materials (usually polymers). An integrated membrane electrode can be produced by precisely docking a porous catalytic membrane with a catalyst deposited thereon with an ion exchange membrane and applying appropriate temperature and pressure to bring the surfaces of the two into close contact.

[0099] In the traditional membrane electrode preparation method, the ionomer and catalyst are mixed to form a slurry which is then coated on the surface of the ion exchange membrane or porous support. This method has many disadvantages: for example, the adhesion between the catalytic layer and the substrate is weak and the interface bonding is not strong enough, which may lead to interface peeling during operation, thereby weakening the stability of the electrode and shortening its service life; the spraying or coating process often makes it difficult to accurately control the thickness and uniformity of the catalytic layer during the coating process, which will adversely affect the mass transfer efficiency and charge transfer efficiency of the electrode, thereby causing fluctuations in the overall performance; in addition, the solution using ionomers also requires complex processes such as multi-step coating, drying and heat treatment, which not only increases the manufacturing cost and prolongs the production cycle, but also faces challenges in the repeatability and consistency of process parameters during large-scale preparation, thereby restricting its potential for large-scale industrial application.

[0100] The hot-pressing transfer process can efficiently combine the porous catalytic membrane loaded with catalyst with the ion exchange membrane, saving process steps, reducing solvent consumption and exhaust emissions, making the combination of the catalyst and the film more stable, and effectively solving the problem of catalytic layer shedding. At the same time, in the large-scale preparation process, the porous catalytic membrane can be prepared independently, and then the mature hot-pressing transfer process can be used to achieve standard "assembly" of the membrane electrode assembly, with good repeatability and consistency, and feasibility of large-scale industrial application.

[0101] In some embodiments, in the hot pressing transfer process, the processing temperature can be selected to be 100°C-130°C to avoid catalyst degradation or membrane material damage caused by excessively high temperature, and to prevent weak bonding caused by too low temperature; the pressure applied during hot pressing can be selected to be 2-5MPa to ensure that the catalyst layer can be evenly transferred to the surface of the ion exchange membrane, while avoiding excessive deformation of the porous catalytic membrane or damage to the catalyst layer; the hot pressing time can be selected to be 1-10min.

[0102] In some other embodiments, the membrane electrode assembly can also be prepared by the following method:

[0103] A solution or dispersion containing ion exchange membrane material is applied to at least one surface of the porous catalyst membrane by coating, casting or pouring, and an ion exchange membrane is formed on the porous catalyst membrane after solidification.

[0104] This process can significantly improve the bonding strength between the porous catalytic membrane and the ion exchange membrane by directly preparing the ion exchange membrane on the surface of the porous catalytic membrane.

[0105] The present application includes, but is not limited to, the following exemplary embodiments.

[0106] Embodiment 1, a porous catalytic membrane, includes a porous polymer membrane formed by randomly arranged nanofibers interweaving, and a catalyst covering the surface of the nanofibers.

[0107] Embodiment 2: The porous polymer membrane is prepared using ultra-high molecular weight polyethylene, the molecular weight of which is 1 to 15 million g / mol.

[0108] Embodiment 3, the porous ultra-high molecular weight polyethylene film is prepared by the following process steps:

[0109] Mixing petrolatum, ultra-high molecular weight polyethylene and an antioxidant, wherein the petrolatum comprises vaseline, white petrolatum or a semi-solid mixture of hydrocarbons;

[0110] stirring petrolatum, ultra high molecular weight polyethylene, and an antioxidant to form a suspension;

[0111] feeding the suspension into an extruder to produce gel filaments;

[0112] pressing the gel filaments to form a gel film;

[0113] stretching the gel film to a preset size;

[0114] placing the stretched gel film under an annealing temperature; and

[0115] Extraction of petrolatum from stretched gel films.

[0116] Embodiment 4, referring to Embodiment 3, adopts other polyolefins to prepare porous polymer membrane, such as polypropylene, polybutene, olefin binary copolymer, olefin multi-copolymer, etc.

[0117] Embodiment 5: When preparing the porous polymer membrane, a stretching force is applied to the polymer material in two mutually perpendicular directions so that the obtained porous polymer membrane is biaxially oriented.

[0118] Embodiment 6: When preparing a porous polymer membrane, the annealing temperature and cooling rate are controlled to form a shish-kebab structure of nanofibers.

[0119] Embodiment 7 uses a porous polymer membrane with a pore size in the range of 15-500nm.

[0120] Embodiment 8 uses a porous polymer membrane with a porosity ranging from 15% to 90%.

[0121] Embodiment 9 uses a porous polymer membrane with a tensile strength in the range of 100-2000 MPa.

[0122] Embodiment 10 uses a porous polymer membrane with an elongation at break of 5%-300%.

[0123] Embodiment 11 uses a porous polymer membrane with nanofiber diameters in the range of 1-100 nm.

[0124] Embodiment 12 uses a porous polymer membrane with a thickness in the range of 15-500nm.

[0125] Embodiment 13, based on the previous embodiment, a catalyst is deposited on the surface of the nanofibers of the porous polymer membrane; the catalyst is a transition metal, or a transition metal alloy, or a compound formed by a transition metal and a VA group or VIA group element.

[0126] In Embodiment 14, the catalyst selected is a hydrogen evolution catalyst.

[0127] In implementation scheme 15, the catalyst selected is an oxygen evolution catalyst.

[0128] Embodiment 16, adopts the process of magnetron sputtering to deposit the catalyst on the porous polymer membrane.

[0129] Embodiment 17, uses the evaporation process to deposit the catalyst on the porous polymer membrane.

[0130] Embodiment 18, using the atomic layer deposition process to deposit the catalyst on the porous polymer membrane.

[0131] Embodiment 19, the catalyst particles are evenly dispersed in a mixed solution of a dispersant and a binder, and the catalyst is deposited on the porous polymer membrane using a solution dipping process.

[0132] Embodiment 20, the catalyst particles are evenly dispersed in a mixed solution of a dispersant and a binder, and the catalyst is deposited on the porous polymer membrane using a spray deposition process.

[0133] In implementation scheme 21, the catalyst precursor is uniformly dispersed in a sol system, and the catalyst is deposited on the porous polymer membrane by a sol-gel spin coating process.

[0134] Embodiment 22, a layer of carbon film or other conductive material is prepared in advance on the surface of the porous polymer membrane, which is placed in an electrolytic cell, and a catalyst is deposited on the porous polymer membrane using an electrochemical deposition process.

[0135] Embodiment 23, by promoting nucleation through the surface functional groups or pre-coating of the porous polymer membrane, a catalyst is directly synthesized on the nanofibers of the porous polymer membrane using a chemical in situ growth process.

[0136] Embodiment 24, based on the above-mentioned catalyst deposition process, the catalyst loading is 0.01-0.5 mg / cm 2 .

[0137] Embodiment 25, a membrane electrode assembly includes an ion exchange membrane and an anode catalyst layer and a cathode catalyst layer respectively bonded to both sides of the ion exchange membrane, at least one of the anode catalyst layer and the cathode catalyst layer is a porous catalyst membrane.

[0138] Embodiment 26, the porous catalytic membrane is combined with the ion exchange membrane by using a hot pressing transfer process.

[0139] In implementation scheme 27, the processing temperature of hot pressing transfer is selected to be 100° C.-130° C., the pressure applied during hot pressing is 2-5 MPa, and the hot pressing time is 1-10 min.

[0140] Embodiment 28, based on Embodiment 26, a solution or dispersion containing ion exchange membrane material is applied to at least one surface of a porous catalytic membrane, and an ion exchange membrane is formed on the porous catalytic membrane after solidification.

[0141] Embodiment 29, a water electrolysis device, includes the membrane electrode assembly provided in the above embodiment, and correspondingly arranged gas diffusion layers, bipolar plates, and necessary seals, gas separation and processing components, etc.

[0142] Embodiment 30, a water electrolysis device, see Figure 5 , specifically including an anode plate 100, a cathode plate 200 and a membrane electrode assembly 600; the anode side of the membrane electrode assembly 600 is provided with a titanium felt 400 for gas diffusion, the cathode side is provided with a carbon paper 500 for gas diffusion, a sealing gasket 300 is provided between the titanium felt 400 and the anode plate, and a sealing gasket 300 is also provided between the carbon paper 500 and the cathode plate; an oxygen gas processing assembly and an oxygen outlet 101 are provided inside the anode plate 100, and a hydrogen gas processing assembly and a hydrogen outlet 201 are provided inside the cathode plate 200; the membrane electrode assembly 600 adopts the membrane electrode assembly provided by the aforementioned embodiment.

[0143] Embodiment 31, a fuel cell, comprising the porous catalytic membrane or membrane electrode assembly provided in the above embodiments; for example, the porous catalytic membrane can be loaded on the electrode surface of the fuel cell to accelerate the electrochemical reaction on the electrode; the membrane electrode assembly is suitable for a proton exchange membrane fuel cell or an alkaline anion exchange membrane fuel cell.

[0144] Embodiment 32, an ion membrane electrolyzer comprises the porous catalytic membrane or membrane electrode assembly provided in the above embodiments.

[0145] Embodiment 33, a large-scale energy storage device (such as an all-vanadium liquid flow battery), includes the porous catalytic membrane or membrane electrode assembly provided by the previous embodiment.

[0146] Embodiment 34, an electrochemical sensor, comprising the porous catalytic membrane or membrane electrode assembly provided in the previous embodiments, is used to detect gases such as carbon dioxide and nitric oxide.

[0147] Embodiment 35, a flexible sensor or flexible energy device, comprising the porous catalytic membrane or membrane electrode assembly provided by the previous embodiment.

[0148] Based on the foregoing embodiments and implementation schemes, the present application also proposes the following specific embodiments to explain in detail the methods, applications and technical effects of the present application. The following specific embodiments are not limitations of the present application, and those skilled in the art may make adjustments in combination with other embodiments or implementation schemes of the present application.

[0149] Example

[0150] The purpose of this embodiment is to Figure 1The ultra-high molecular weight polyethylene film shown was used as a carrier to prepare a Pt-PE electrode (i.e., an ultra-high molecular weight polyethylene film loaded with a Pt catalyst) and used for PEM water electrolysis.

[0151] First, an ultra-high molecular weight polyethylene film with suitable thickness, pore structure and mechanical parameters is selected; preferably, the porosity of the ultra-high molecular weight polyethylene film is in the range of 50%-70%, and the thickness of the ultra-high molecular weight polyethylene film is in the range of 15-500nm, and the porosity range and thickness range are suitable for uniformly depositing the catalyst on the nanofibers from the outside to the inside of the film by magnetron sputtering; the glass transition temperature of the ultra-high molecular weight polyethylene film is about -120°C, and the melting temperature is about 135°C, which meet the temperature conditions of magnetron sputtering (the temperature required for magnetron sputtering is usually less than 100°C). Therefore, during the deposition process, the film can maintain the stability of its size and structure, and effectively avoid film deformation or abnormal distribution of precious metals caused by thermal effects.

[0152] The surface of ultra-high molecular weight polyethylene film is modified by corona treatment, plasma treatment and other methods to form polar groups on the surface of the film, thereby enhancing the adhesion and stability of the catalyst.

[0153] Magnetron sputtering Pt catalyst: The magnetron sputtering device used in this embodiment is shown in Figure 4 The magnetron sputtering device includes a cavity 1, a target electrode 3, a rotating stage 4, and a power supply 5. The target 3 is a Pt target, and the target 3 is installed on the target electrode 3. The rotating stage 4 is used to carry the ultra-high molecular weight polyethylene film on which the catalyst is to be deposited. The magnetron sputtering bombards the Pt target through Ar ions 6, so that Pt atoms 7 are sputtered out from the target and deposited on the nanofibers of the ultra-high molecular weight polyethylene film to form a uniform catalyst layer.

[0154] After the sputtering chamber is evacuated to a preset value, in an Ar atmosphere with a flow rate of 30-50sccm (preferably 30ssccm), by applying a 10-150W (preferably 50W) power pulse alternating current, the Ar gas is ionized under high pressure, and the Ar ions move at high speed under the action of a strong electric field and bombard the Pt target to obtain free Pt atoms with a certain initial moving speed. The Pt atoms bombard the ultra-high molecular weight polyethylene film in a high-speed moving state to form a catalyst layer on the nanofibers, and the thickness sputtering rate can be controlled at 12-15nm / min; in this embodiment, Pt catalysts are magnetron sputtered on both surfaces of the ultra-high molecular weight polyethylene film, and the deposition thickness and uniformity of the catalyst can be precisely controlled by the magnetron sputtering process; the Pt-PE electrode prepared in this embodiment is as follows Fig.16 shown.

[0155] Preparation of PEM membrane electrode assembly by hot pressing transfer: the ultra-high molecular weight polyethylene film deposited with Pt catalyst is connected to the proton exchange membrane, and a certain temperature and pressure are applied to make the catalyst layer and the surface of the proton exchange membrane closely bonded to form an integrated electrode; the temperature of hot pressing transfer is controlled between 100°C and 130°C, the pressure applied during hot pressing is controlled at 2-5MPa, and the hot pressing time is 1-10min; the PEM membrane electrode assembly prepared in this embodiment is as follows Fig.17 shown.

[0156] This embodiment adopts a dry process to prepare the membrane electrode assembly, and the hot pressing transfer process does not use solvents or adhesives, thereby reducing solvent consumption and exhaust emissions, avoiding solvent residues, meeting green environmental protection requirements, and being able to efficiently combine the catalyst and the film together, saving time and avoiding the problem of unevenness during the coating process; in addition, the bonding between the catalyst and the film is more stable, and the problem of catalyst layer shedding is effectively solved.

[0157] Furthermore, the Pt-PE electrode and PEM membrane electrode assembly prepared in this example were characterized and performance tested.

[0158] The morphology of Pt-PE electrode is shown in Figure 2 and Figure 3 , Figure 2 The surface SEM images of Pt-PE electrodes with different sputtering thicknesses show that the Pt catalyst is evenly covered on the nanofiber surface of the ultra-high molecular weight polyethylene film; Figure 3 The cross-sectional SEM image of the PEM membrane electrode assembly prepared by hot pressing transfer of Pt-PE electrode is shown in Figure 2. Figure 3 As shown, the proton exchange membrane is located below the Pt-PE electrode, and the Pt-PE electrode is tightly fitted to the proton exchange membrane with no gap between the two. In this embodiment, four Pt-PE electrode experimental groups with sputtering thicknesses of 30nm, 35nm, 40nm and 45nm are designed, and two control groups of commercial Pt foil (Ptfoil) and commercial Pt / C catalyst (Commerial Pt / C) are set up.

[0159] The above experimental group and control group were subjected to electrochemical tests under a three-electrode system. The test results are shown in Figure 6-Figure 9 .

[0160] Figure 6 The linear sweep voltammetry (LSV) curves of the experimental group and the control group in the hydrogen evolution reaction (HER) are shown in Figure 2. Figure 7This is a column comparison chart of the overpotential of the experimental group and the control group in the hydrogen evolution reaction. It can be seen that the Pt-PE electrodes in the experimental group have a lower overpotential (close to the Pt / C catalyst), which meets the catalytic requirements of cathode hydrogen evolution in electrolyzed water. Among them, the Pt-PE electrode with a sputtering thickness of 40nm has the lowest overpotential (13mV).

[0161] Figure 8 This is a comparison of the linear sweep voltammetry curves of the 40nm Pt-PE electrode and the commercial Pt / C catalyst after 10,000 cyclic voltammetry tests and the initial state. It can be seen that after 10,000 cyclic voltammetry tests, the linear sweep voltammetry curve of the 40nm Pt-PE electrode has little change compared with the initial state. The 40nm Pt-PE electrode has better electrochemical stability than the commercial Pt / C catalyst.

[0162] Fig. 9 Figure 2 is the electrochemical impedance spectroscopy (EIS) of the experimental group and the control group in the hydrogen evolution reaction. The Pt-PE electrodes in the experimental group have a smaller charge transfer resistance, indicating that the kinetic resistance of the electrode reaction is smaller.

[0163] The above experimental group and control group were subjected to electrochemical tests in the PEM water electrolysis device. The test results are shown in Figure 10-15 .

[0164] Fig.10 The voltage-current density curve of 45nm Pt-PE electrode in PEM water electrolysis shows the voltage response at different current densities. It can be concluded from the figure that 3A / cm 2 The operating voltage corresponding to the current density is 1.784V, which is better than the 2016 target of the US DOE (3A / cm 2 The operating voltage is 1.8V).

[0165] Fig.11 The voltage-current density curve of the experimental group in PEM water electrolysis shows the effect of different Pt catalyst sputtering thickness on the working voltage of water electrolysis. It can be seen that with the increase of sputtering thickness, the corresponding working voltage at the same current density is lower, and the electrolysis efficiency is higher.

[0166] Fig.12 This is a comparison chart of the voltage-current density curves of the 45nm Pt-PE electrode and the commercial Pt / C electrode in PEM water electrolysis. At the same current density, the corresponding working voltage of the Pt-PE electrode is lower than that of the Pt / C electrode (at a current density of 4A, the working voltage is 160mV lower). The Pt-PE electrode has a higher electrolysis efficiency when used for PEM water electrolysis.

[0167] Fig.13The voltage-current density curve of 45nm Pt-PE electrode in PEM water electrolysis under different temperature conditions (60℃, 65℃, 70℃, 75℃, 80℃) shows the effect of temperature on the electrolysis voltage. It can be seen that within the range of 60℃-80℃, increasing the temperature is beneficial to reducing the working voltage of water electrolysis and improving the electrolysis efficiency.

[0168] Fig.14 The voltage-current density characteristics of the 45nm Pt-PE electrode in the PEM water electrolysis system were demonstrated to evaluate its durability under high load conditions; 2 At a current density of 1.5 V, 40,000 accelerated aging cycles were performed (alternating between 1.45 V and 1.9 V, with each voltage maintained for 30 seconds), which can simulate the cyclic stress of the electrode in actual applications; the results showed that after 40,000 cycles of accelerated aging, the voltage only decayed by about 41 mV, indicating that the electrode can still maintain excellent stability and durability under high load conditions, which is of great significance to the practical application of PEM water electrolysis.

[0169] Fig.15 This is a long-term stability test data chart of 45nm Pt-PE electrode at different current densities, showing the long-term stability test results of water electrolysis at different current densities. At a lower current density (0.5A / cm²), the voltage is about 1.6V, and there is almost no decay in the test lasting more than 100 hours; at a higher current density (1.8A / cm²), the voltage is about 1.78V, and the decay rate is only 0.026mV / h, indicating that the system can maintain a very stable voltage even under high load; overall, these results show that the electrode has excellent durability and stability under different working conditions.

[0170] From the above characterization and test results, it can be seen that the Pt-PE electrode prepared in this embodiment has excellent catalytic activity, electrochemical stability and electrolysis efficiency in the application of water electrolysis, and is suitable for high-performance, high-reliability and low-cost hydrogen energy production.

[0171] The embodiments described above are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.

Claims

1. A porous catalytic membrane, characterized in that: include: A porous polymer membrane formed by randomly arranged nanofibers interwoven, wherein the porous polymer membrane is made of polyolefin; as well as, A catalyst is covered on the surface of the nanofiber.

2. The porous catalyst membrane according to claim 1, characterized in that: The porous polymer membrane is prepared by the following process steps: Step 1, mixing petrolatum, polyolefin and antioxidant, wherein the petrolatum comprises vaseline, white vaseline or a semi-solid mixture of hydrocarbons; Step 2, stirring petrolatum, polyolefin and antioxidant to form a suspension; Step 3, supplying the suspension to an extruder to produce gel filaments; Step 4, pressing the gel filaments to form a gel film; Step 5, stretching the gel film to a preset size; Step 6, placing the stretched gel film under annealing temperature; Step 7, extracting petrolatum from the stretched gel film.

3. The porous catalyst membrane according to claim 2, characterized in that: The porous polymer membrane is biaxially oriented, and the nanofibers of the porous polymer membrane comprise a shuffle structure.

4. The porous catalyst membrane according to claim 2, characterized in that: The porous polymer membrane is made of ultra-high molecular weight polyethylene, and the molecular weight of the ultra-high molecular weight polyethylene is 1 million to 15 million g / mol.

5. The porous catalyst membrane according to claim 1, characterized in that: The pore size of the porous polymer membrane is 15-500nm.

6. The porous catalytic membrane according to claim 1, characterized in that: The porosity of the porous polymer membrane is 15%-90%.

7. The porous catalyst membrane according to claim 1, characterized in that: The tensile strength of the porous polymer membrane is 100-2000 MPa.

8. The porous catalyst membrane according to claim 1, characterized in that: The elongation at break of the porous polymer film is 5%-300%.

9. The porous catalyst membrane according to claim 1, characterized in that: The diameter of the nanofiber is 1-100 nm.

10. The porous catalyst membrane according to claim 1, characterized in that: The thickness of the porous polymer film is 15-500nm.

11. The porous catalyst membrane according to claim 1, characterized in that: The catalyst loading is 0.01-0.5 mg / cm 2 .

12. The porous catalyst membrane according to claim 1, characterized in that: The catalyst is at least one of a transition metal, a transition metal alloy, and a compound formed by a transition metal and a Group VA or Group VIA element.

13. The porous catalyst membrane according to claim 12, characterized in that: The catalyst is deposited on the surface of the nanofiber by at least one process selected from the group consisting of physical vapor deposition, atomic layer deposition, electrochemical deposition, solution dipping, spray deposition, sol-gel method, and chemical in-situ growth.

14. A membrane electrode assembly, comprising an ion exchange membrane and an anode catalyst layer and a cathode catalyst layer respectively bonded to both sides of the ion exchange membrane, characterized in that: At least one of the anode catalyst layer and the cathode catalyst layer is the porous catalyst membrane according to any one of claims 1 to 13.

15. The membrane electrode assembly according to claim 14, characterized in that: The porous catalytic membrane is combined with the ion exchange membrane through a hot pressing transfer process.

16. The membrane electrode assembly according to claim 15, characterized in that: In the hot pressing transfer process, the processing temperature is 100° C.-130° C., the pressure applied during hot pressing is 2-5 MPa, and the hot pressing time is 1-10 min.

17. The membrane electrode assembly according to claim 14, characterized in that: The ion exchange membrane is prepared by the following method: A solution or dispersion containing ion exchange membrane material is applied to at least one surface of the porous catalyst membrane, and the ion exchange membrane is formed on the porous catalyst membrane after being cured.

18. A water electrolysis device, characterized in that: The invention comprises the porous catalytic membrane according to any one of claims 1 to 13, or the membrane electrode assembly according to any one of claims 14 to 17.

Citation Information

Patent Citations

  • Fuel cell ordered porous nano-fiber single electrode, membrane electrode and preparation method

    CN103413947A

  • Porous electrocatalytic film, and preparation and application thereof

    CN106890676A

  • Metal supported powder catalyst matrix and processes for multiphase chemical reactions

    CN111954574A

  • Preparation method and application of hollow nano groove type membrane electrode

    CN112993349A

  • Cross-temperature-zone membrane electrode and proton exchange membrane fuel cell thereof

    CN114361545A

Cited By

  • Nanofiber membrane for CO2 reduction as well as preparation method and application of nanofiber membrane

    CN121538684A